Proclamation by His Excellency William Fergusson, Lieutenant Governor in and over the colony of Sierra Leone and its dependencies ... : [on offenders in Britain's overseas possessions, being transported to Van Diemen's Land or Norfolk Island] - Sierra Leone. Lieutenant Governor (1845-1846 : Fergusson); Sierra Leone. Colonial Secretary (Freetown, Sierra Leone : [Govt. Printer], 1844)
The proclamation identifies the acts of George IV [1826] and Victoria [1840] as the primary statutory instruments which state that convicts already sentenced to transportation and originating from Britain's overseas possesesions can be transported to the same places as convicts transported from Great Britain. Under this authority Fergusson in this proclamation states that transportation will be either to Van Diemen's Land or Norfolk Island. Convicts transported from other British possessions to Australia was rare.
Caption title.
"26th October 1844"
Also available online
Keywords: Transportation of convicts -- Sierra Leone -- History -- Sources; Transporation of convicts -- Tasmania -- History -- Sources; Transportation of convicts -- Norfolk Island -- History -- Sources; Sierra Leone -- History -- Sources